Roadnoise: The old friends tour - Morgan, Lee (Auckland University of Technology, 2006)
My thesis a project that researches the part memory has on recollecting and recounting memoryas narratives, using the road trip and Jack Kerouac’s beat novel On the road (1955) as a motivation to translate Kerouac’s spontaneous ideology, into a visual medium. The road trip philosophy is one of chance encounters, it is not a fully constituted, pre planned excursion, but rather an approach that allows a fluidity and spontaneity with people and places as they occur. The project explores the notion of intertextuality forwarded by Kristeva (1986) and the artifact Archimedes palimpsest, the layering of text over partially obliterated text, and the influence of computer technologies found within the general population. The project culminates in video: The old friend’s tour 2006.
Keywords: Kerouac, Jack, 1922-1969; On the road; Travel in art; Painting; Photography; Artistic; Art installations